CULTURAL STIGMA AGAINTS TAMIL WOMEN IN INDIA - Khaula Abubakar; Saprudin (Universitas Suryakancana, 2026)
This study aims to analyze the cultural stigma experienced by Tamil women in the film Pad Man. This film depicts the struggle of a man and husband of a woman from the Tamil tribe who still believes in the customs there, where the man tries to change people's views on menstruation and sanitary napkins. This research uses a descriptive qualitative method with a content analysis approach to identify the cultural stigma that appears in the movie Pad Man.